1988
DOI: 10.1055/s-2007-1018130
|View full text |Cite
|
Sign up to set email alerts
|

Gastroscopic Screening for Gastric Carcinoids and Carcinoma in Pernicious Anemia

Abstract: Among 196 patients examined in 1972-1985 because of pernicious anemia (PA), 105 patients under the age of 76 years were invited for gastroscopic screening, and 71 patients (68%) participated. Gastroscopy revealed carcinoid tumor(s) in 5 patients (7%) but no case of carcinoma. In addition, one patient with gastric carcinoid, 5 patients with adenocarcinomas and one with a concomitant carcinoid and carcinoma had already been diagnosed earlier in the overall PA group on the basis of clinical symptoms. Thus, within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
70
1
6

Year Published

1992
1992
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(79 citation statements)
references
References 0 publications
2
70
1
6
Order By: Relevance
“…An older study reported an annual incidence of 2 %, observing 8 new cases of T1-GCs in 416 patient-years [7]. In the above cited study, pernicious anemia was present in almost 50 % of patients with T1-GCs [9], while previous studies exclusively included patients with this condition [7,8,[10][11][12].…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…An older study reported an annual incidence of 2 %, observing 8 new cases of T1-GCs in 416 patient-years [7]. In the above cited study, pernicious anemia was present in almost 50 % of patients with T1-GCs [9], while previous studies exclusively included patients with this condition [7,8,[10][11][12].…”
Section: Introductionmentioning
confidence: 78%
“…Gastrin acts as a growth type factor for enterochromaffin-like cells, which in ABG are chronically induced to proliferate through a multistep process passing from hyperplasia to dysplasia and then to carcinoids [3][4][5]. Long-term observational studies assessing the incidence of T1-GCs in ABG patients are scarce [6][7][8]. In a recent cohort study, ABG patients were followed up for 1,463 person-years, reporting an annual incidence rate of 0.4 % for type I gastric carcinoids [9].…”
Section: Introductionmentioning
confidence: 99%
“…Autoimmune gastritis is also a risk factor for gastric neuroendocrine tumors (carcinoids) and gastric cancer development (2). Gastric cancer incidence ranges from 1 to 3% for gastric carcinoma and from 2 to 12.5% for carcinoid tumors in patients with AIG with or without pernicious anemia (3)(4)(5)(6). Gastric carcinoid tumors that occur in patients with AIG are labeled as type I gastric carcinoids.…”
Section: Introductionmentioning
confidence: 99%
“…7 What of the patients with normoblastic marrows with either a normal blood film or a raised mean cell volume who have a low serum cobalamin concentration and malabsorb cobalamin? They probably have gastric atrophy.…”
Section: Pernicious Anaemiamentioning
confidence: 99%